Caracterização da maciez da carne por análises proteômicas e moleculares - Oliveira, Leonardo Guimarães de (2016)
The protein profile of hornless Nellore cattle from a segregating population for meat tenderness of extremes shear force, low extreme group (M) and extreme high (D) group, showed differentially expressed proteins. They had greater relative abundance of proteins of the glycolytic process in group M and proteins of the oxidative metabolism evidenced more expressed in group D, fact that probably is correlated to the final tenderness of the meat. Only identified in group D, the cytochrome c protein indicates induction of the apoptotic process in this group of animals. Structural proteins were identified in group M, indicating a possible greater proteolysis. Calpastatin was only identified in group D, this protein is highly related to the final meat tenderness because it is a natural inhibitor of the calpain. Separation of calpastatin by ion exchange column chromatography of two different muscles described two peaks of calpain inhibitory activity: peak 1 (CAST1) and peak 2 (CAST2). CAST 1 activity increased during the post-mortem period in Triceps brachii and showed no difference between days in Longissimus dorsi and on the other hand, total activity of calpastatin and CAST 2 decreased during post-mortem aging. The 115 kDa band of calpastatin decreased its intensity during post-mortem aging in both muscles with more than 70% of the change occurring on the first day. The mitochondrial ATP synthase beta subunit proteins increased and Succinyl CoA ligase decreased after aging and Adenylate kinase isoenzyme decreased on day 7. Calpastatin peaks had weak phosphorylated bands and had different IP and MW patches than 2D-SDS -PAGE. During the purification process of the calpastatin peaks the activity per mg of protein increased but lost half of the total activity presented during the first purification step. For peak 2 of calpastatin the specific activity increased 139.8 times and at the end of this process 36% of the total activity remained. Purified calpastatin was identified on the second-size gel having a molecular weight similar to the western blot. Spots from calpastatin peak 1 and two from calpastatin peak 2 were identified as peptides belonging to the calpastatin molecule. Sequence of peptides identified in Spot from purified peak 1 as part of the inhibitory domain III and IV and of the C-terminus and from the purified peak 2 a sequence of peptides identified as part of the inhibitory domain I, II and III. These results lead us to believe that both peaks, in this case, are degradation products of the intact molecule, and probably the small peptides are broken down during the process. The results of the present study show that purification of distinct forms of active calpastatin is possible, however, the intact form of calpastatin was not present in this purification. The presence of peptides was not conclusive to determine the origin and composition of each active peak.